2007
DOI: 10.5465/amle.2007.24401702
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Predictive Validity of the Graduate Management Admission Test (GMAT) and Undergraduate Grade Point Average (UGPA) for Graduate Student Academic Performance.

Abstract: Considerable debate both within and outside of academic circles surrounds the validity of standardized tests for predicting student performance in graduate business schools. This meta-analysis aggregates the existing literature on the validity of the two most heavily used predictors in business school admissions: the GMAT and undergraduate grade point average. Results based on over 402 independent samples across 64,583 students indicate that the GMAT is a superior predictor to UGPA and that the two combined yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 69 publications
6
72
0
4
Order By: Relevance
“…They found that a vast majority of these relationships were strong even after controlling for factors like socioeconomic status. On the whole, both HSGPA and standardized tests have been shown to have predictive validity in determining a variety of academic performance outcomes (e.g., Bridgeman, McCamley-Jenkins, & Ervin, 2000;Kuncel, Credé, & Thomas, 2007;Kuncel & Hezlett, 2007;Kuncel et al, 2001Kuncel et al, , 2004.…”
mentioning
confidence: 99%
“…They found that a vast majority of these relationships were strong even after controlling for factors like socioeconomic status. On the whole, both HSGPA and standardized tests have been shown to have predictive validity in determining a variety of academic performance outcomes (e.g., Bridgeman, McCamley-Jenkins, & Ervin, 2000;Kuncel, Credé, & Thomas, 2007;Kuncel & Hezlett, 2007;Kuncel et al, 2001Kuncel et al, , 2004.…”
mentioning
confidence: 99%
“…Recent studies on admission processes to MBA programs use, mainly, standardized tests for measuring cognitive abilities, among them the Graduate Management Admission Test (GMAT), the most widely used by universities and business schools around the world as admission requirement for their programs (Gropper, 2007;Koys, 2010;Kuncel et al, 2007).…”
Section: Cognitive Abilitymentioning
confidence: 99%
“…To accomplish this, admission systems must perform two main tasks: (a) choosing the best variables to predict academic performance (AP) of applicants and (b) finding the best combination of those predictors for making admission decisions (Kuncel, Credé, & Thomas, 2007). Traditionally, admission systems of educational organizations have privileged previous academic 669395S GOXXX10.1177/2158244016669395SAGE OpenDakduk et al…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis examined graduate business students' academic success. The predictors were undergraduate grade point average (GPA) and the aptitude test required for graduate degrees in business schools, the Graduate Management Admission Test (GMAT) (Kuncel, Crede, & Thomas, 2007). They showed that both predictors combined contribute unique and substantial variance in predicting first-year graduate GPA and overall GPA of graduate students.…”
Section: Educational Achievementmentioning
confidence: 99%